Aging and inequality: The link and transmission mechanisms. Issue 3 (21st May 2018) - Luo, Zhi; Wan, Guanghua; Wang, Chen; Zhang, Xun
Abstract: There exists a shortage of rigorous empirical analyses that focus on the aging‐to‐inequality transmission mechanisms although both developed and some developing countries have been confronted with the challenge of population aging. Using cross‐country panel data covering the period of 1975 to 2015, this paper contributes to the literature by directly modeling the relationship between aging and inequality and exploring the transmission mechanisms. Our estimation results show that (1) Aging worsens income distribution; (2) This adverse impact is attributable to its negative correlation with the share of labor income that in general is more equally distributed than capital income; (3) The labor share‐reducing effect of aging can be further attributed to the significant and negative impact of aging on both labor input or supply and wage or labor productivity; and (4) Our findings are robust to changes in model specifications, use of different indicators of aging, different inequality and labor share data sources.